2014
DOI: 10.1038/clpt.2014.64
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy–Induced Mitochondrial Toxicity: Potential Mechanisms Beyond Polymerase-γ Inhibition

Abstract: We hypothesized that competition between NRTI-triphosphate and endogenous deoxyribonucleoside triphosphate (dNTP) may lead to depletion of dNTP pools and mitochondrial dysfunction independent of Pol-γ inhibition. We collected peripheral blood mononuclear cells from 75 adults (25 cases: HIV-infected with mitochondrial toxicity, 25 HIV-infected positive controls, and 25 HIV-negative controls). We observed statistically significant individual and group differences in ribonucleotide (RN) and deoxyribonucleotide (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 48 publications
(51 reference statements)
3
36
0
Order By: Relevance
“…Therefore, deficiencies in TK2 or dGK activity are likely responsible for the observed mtDNA depletion in these HIV patients, independent of mtDNA polymerase inhibition (Fig. 7), in line with a recent report showing that antiviral therapy caused depletion of both ribonucleotide and deoxynucleotide pools in HIV patients (12).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, deficiencies in TK2 or dGK activity are likely responsible for the observed mtDNA depletion in these HIV patients, independent of mtDNA polymerase inhibition (Fig. 7), in line with a recent report showing that antiviral therapy caused depletion of both ribonucleotide and deoxynucleotide pools in HIV patients (12).…”
Section: Discussionsupporting
confidence: 89%
“…The mechanism underlying the mitochondrial toxic effects of these types of nucleoside analogs has been postulated to occur via the inhibition of mitochondrial DNA (mtDNA) polymerase by the triphosphates of these analogs. However, recent studies using peripheral blood mononuclear cells from HIV-infected individuals treated with antiviral agents showed that depletion of both ribonucleotide and deoxynucleotide pools may be responsible for the observed mitochondrial toxicity independent of mtDNA polymerase inhibition (12). Other studies suggest that inhibition of mitochondrial TK2 and dGK may be a major contributing factor in nucleoside analog-induced mitochondrial toxicity, and the symptoms of AIDS patients treated with AZT or ddI resemble those reported for MDS patients (5,6,10,11).…”
mentioning
confidence: 99%
“…During the last decades, many studies have focused on the atherogenic effect of ART, especially PI-containing drugs [74]. ART could result in mitochondrial abnormalities by inhibiting the mitochondrial DNA polymerase, which would lead to respiratory chain dysfunction and reduction of cell energy [75]. Mitochondrial respiratory chain inhibition resulted in adipocyte abnormality, which is related to lipodystrophy syndrome and hyperlipemia [76].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria have been closely linked to HIV infection, as a target of the deleterious effects of both HIV 2 and antiretroviral therapy (ART) 3 in relation to their involvement in the development of apoptosis. Mitochondrial and apoptotic alterations have been widely described in both naïve and treated patients in vivo 4, 5.…”
Section: Introductionmentioning
confidence: 99%